Why a buyer is much more than a cost-killer. Issue 2 (13th February 2017) - Poissonnier, Hugues
Abstract : Purpose: This paper aims to show the evolutions of the missions given to buyers. Design/methodology/approach: This study uses a historical approach. Findings: Cost-killing is less and less the more important part of the buyer's job. Originality/value: This paper is aimed at showing the importance of alternative missions given to buyers, in addition to the traditional mission consisting in reducing costs. More and more supply security and value creation are considered as more strategic missions for purchasing.